Case Report: Expansion of the POLD1-related polymerase proofreading-associated polyposis spectrum: first report of duodenal adenocarcinomas and characterization of two likely pathogenic variants - Folletet, Anais; Helyon, Morgane; Privat, Maud; Uhrhammer, Nancy; Gay-Bellile, Mathilde; Cavaille, Mathias; Ponelle-Chachuat, Flora; Bidet, Yannick; Lepage, Mathis (Frontiers in Oncology, 2025)
BackgroundPolymerase proofreading-associated polyposis (PPAP) is a rare autosomal dominant cancer predisposition syndrome caused by germline pathogenic variants in POLE or POLD1. While colorectal and endometrial cancers are the most frequent manifestations, the full tumor spectrum of POLD1-related PPAP remains incompletely defined.Case presentationWe describe two families carrying germline POLD1 variants classified as likely pathogenic. A novel missense variant c.1481T>G p.(Ile494Ser) and a recurrent missense variant c.1204G>A p.(Asp402Asn) were identified within the exonuclease domain. Both variants exhibited features consistent with pathogenicity, including high tumor mutational burden (TMB) and SBS10d mutational signature. Affected carriers developed colorectal and endometrial cancers, but also duodenal adenocarcinomas: this is the first report of this tumor type in germline POLD1 carriers.ConclusionsOur report expands both the phenotypic and molecular spectrum of POLD1-associated PPAP by documenting the first duodenal adenocarcinomas in germline carriers and describing a novel variant. These findings emphasize the need for systematic upper gastrointestinal surveillance, support the systematic reporting of rare POLD1 variants to refine genotype–phenotype correlations, and underline the potential therapeutic relevance of identifying carriers in the context of immunotherapy.